O discurso iluminista da exclusão digital: Crítica do Mundaneum informático Pós-Fordista de Knoxville, Tennessee - Berrio-Zapata, Cristian [UNESP]; Pomim Valetim, Marta Lígia; Gonçalves Santana, Ricardo César [UNESP]; Hernandez Humaña, Iván Dario (My University, 2015)
This article discusses the project of the Information Society and the discourses that undergo it, as part of a political and ideological conception universalized by those countries that created and dominate computer technology, which is in turn is aligned with the Post-Fordist industrial capitalist order and its emphasis on economic accumulation and consumerism. We explain how information technology creates routines and legitimate social orders, taking for analyzes the case of the Clinton-Gore policy in the United States, when the discourse of the computer society was associated with the development and social welfare. This association is revealed in the speech made by Clinton in the city of Knoxville in year 1996. There we see the beginnings of the concern about the Digital Divide as a new form of social disease that prevents the passage to a better world, focused on productivity, accumulation and consumption in information-dense societies. This generates a clash between the industrial-graph-centric world and the oral-pre-industrial communities, as a result of attempting to transplant the institutional forms of the developed West. We explain the pillars of the new computerized order, and how they replaced previous epic narratives creating techno-deterministic or techno-phobic discourses in prejudice of more critical approaches. We identify the effects such deterministic discourses that connote the association between the Information Society, welfare and development, questioning the urgency of deploying this system at global level without profound critical discussion, clear goals focused on the benefit of the human beings, and the open participation of the users of the system. centric world and the oral-pre-industrial communities, as a result of attempting to or techno-phobic discourses in prejudice of more critical approaches. We identify the effects such deterministic discourses that connote the association between the Information Society, welfare and development, questioning the urgency of deploying this system at global level without profound critical discussion, clear goals focused on the benefit of the human beings, and the open participation of the users of the system.
The illuminist discourse of the digital divide: A critic to the Post-Fordist informatic Mundaneum from Knoxville, Tennessee
Keywords: Digital divide; Discourse; Information society